Structural mechanism of heavy metal-associated integrated domain engineering of paired nucleotide-binding and leucine-rich repeat proteins in rice - Guo, Liwei; Mu, Yuanyu; Wang, Dongli; Ye, Chen; Zhu, Shusheng; Cai, Hong; Zhu, Youyong; Peng, Youliang; Liu, Junfeng; He, Xiahong (Frontiers in Plant Science, 2023)
Plant nucleotide-binding and leucine-rich repeat (NLR) proteins are immune sensors that detect pathogen effectors and initiate a strong immune response. In many cases, single NLR proteins are sufficient for both effector recognition and signaling activation. These proteins possess a conserved architecture, including a C-terminal leucine-rich repeat (LRR) domain, a central nucleotide-binding (NB) domain, and a variable N-terminal domain. Nevertheless, many paired NLRs linked in a head-to-head configuration have now been identified. The ones carrying integrated domains (IDs) can recognize pathogen effector proteins by various modes; these are known as sensor NLR (sNLR) proteins. Structural and biochemical studies have provided insights into the molecular basis of heavy metal-associated IDs (HMA IDs) from paired NLRs in rice and revealed the co-evolution between pathogens and hosts by combining naturally occurring favorable interactions across diverse interfaces. Focusing on structural and molecular models, here we highlight advances in structure-guided engineering to expand and enhance the response profile of paired NLR-HMA IDs in rice to variants of the rice blast pathogen MAX-effectors (Magnaporthe oryzae AVRs and ToxB-like). These results demonstrate that the HMA IDs-based design of rice materials with broad and enhanced resistance profiles possesses great application potential but also face considerable challenges.